Evidence? We Don’t Need No Stinkin’ Evidence! How Ambiguity in Some States’ Anti-SLAPP Laws Threatens to DeFang a Popular and Powerful Weapon Against Frivolous Litigation - Sherwin, Robert T. (The Columbia Journal of Law & the Arts, 2017)
For nearly thirty years, states have been adopting laws that attempt to stop rich, sophisticated parties from using costly litigation as a weapon to punish and silence their less-affluent critics. Known as “anti-SLAPP” statutes, these measures have been incredibly effective in forcing certain plaintiffs to bring forth evidence at an early stage of litigation to show their claims have merit. Unfortunately, a troubling trend has emerged. Some states’ courts are interpreting particular language within their anti-SLAPP laws to allow plaintiffs to survive early dismissal by merely pointing to unproven and unsworn-to allegations in their pleadings. This movement is on the rise as Congress recently considered a federal anti-SLAPP bill that just so happens to feature this same ambiguous language. This Article explores how state courts are arriving at entirely opposite holdings despite sharing statutory language that is identical in form and purpose. Ultimately, I offer specific suggestions about how Congress and state legislatures can fix their laws to avoid uncertainty and fully effectuate the purpose of anti-SLAPP legislation.